(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article analyzes the role of information technology in developing students’ critical thinking skills. As digital technologies become increasingly important in modern education, it is essential for students to acquire the ability to think independently, analyze problems, and develop alternative solutions. The article explores the impact of information technologies on the learning process, their influence on students’ cognitive development, and their contribution to enhancing critical thinking. Additionally, modern approaches and methods related to this topic are discussed.